2017
DOI: 10.1088/1748-605x/aa78d0
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan-based hydrogels for developing a small-diameter vascular graft: in vitro and in vivo evaluation

Abstract: Chitosan-based hydrogels displayed promising in vitro biocompatibility and hemocompatibility properties as well as in vivo short-term performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
1
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 42 publications
1
20
1
3
Order By: Relevance
“…S1). Exclusion of duplicates and then systematic screening of title and abstract using the Covidence platform revealed 321 studies, which was finally limited by thorough text reading to 68 studies based on inclusion criteria . These studies represented a total of 873 grafts: 258 occluded and 615 patent grafts at the end of the evaluation period.…”
Section: Resultsmentioning
confidence: 99%
“…S1). Exclusion of duplicates and then systematic screening of title and abstract using the Covidence platform revealed 321 studies, which was finally limited by thorough text reading to 68 studies based on inclusion criteria . These studies represented a total of 873 grafts: 258 occluded and 615 patent grafts at the end of the evaluation period.…”
Section: Resultsmentioning
confidence: 99%
“…The results showed that the prepared hydrogels were hemocompatible and did not induce any significant hemolysis in comparison with the negative control groups ( p < .3). The hemocompatibility of chitosan‐based hydrogels has been reported in various studies 46–48 . As shown in Figure 4, the incorporation of tEDTA slightly increased the hemolysis percent, while adding AV reduced the hemolysis.…”
Section: Resultsmentioning
confidence: 71%
“…The hemocompatibility of chitosan-based hydrogels has been reported in various studies. [46][47][48] As shown in Figure 4, the incorporation of tEDTA slightly increased the hemolysis percent, while adding AV reduced the hemolysis. Moreover, the difference between the samples (other than positive control) was not statistically significant (p < .4).…”
Section: Hemocompatibility Resultsmentioning
confidence: 79%
“…Results from in vivo studies in small and large animals (rat and sheep) and in vitro studies of chitosanbased hydrogels indicated that the hydrogel exhibited good hemocompatibility properties in vivo and promising in vitro biocompatibility. 85 The electrical properties of implanted grafts are significant challenges for the regeneration of infarcted heart tissue. Distribution of AuNPs throughout chitosan is one way to enhance electrical coupling between adjacent cells within chitosan scaffolds.…”
Section: Chitosanmentioning
confidence: 99%